Analysis of the influence of macroeconomic factor on long-term and short-term fluctuation of the Indonesian stock exchange (BEI) using the error correction method (ECM) approach - Roosaleh Laksono,; Suryana,; Paulus Sugianto Yusuf, (Technium Social Sciences Journal, 2024)
This research aims to empirically test the influence of the short-term equilibrium relationship and long-term equilibrium relationship of economic growth, interest rate, inflation, and exchange rate on IHSG (IDX Composite) using empirical Error Correction Model (ECM) data from 2000 to 2023. During the observation period, the macroeconomic variables showed no significant influence on the movement of the IHSG (IDX Composite) in the short-term equilibrium relationship, whereas in the long-term equilibrium relationship almost all variables, namely economic growth, interest rate, and exchange rate, had a significant influence on the IHSG ( IDX Composite), while inflation has no short or long term effect on the IHSG.